MACROPHYTE BIOASSAY APPLICATIONS FOR MONITORING PESTICIDES IN THE AQUATIC ENVIRONMENT - Della Vechia, J. F.; Cruz, C. [UNESP]; Silva, A. F. [UNESP]; Cerveira Jr, W. R. [UNESP]; Garlich, N. [UNESP] (Univ Federal Vicosa, 2016)
The objective of this study was to evaluate the feasibility of the use of macrophytes Lemna minor and Azolla caroliniana as biomarkers of exposure (acute toxicity) for atrazine, bentazon + imazamox and clomazone, insecticide alpha cypermethrin + teflubenzuron and fungicides pyraclostrobin and mixture pyraclostrobin + epoxiconazole, as well as the risk for environmental intoxication. For this purpose, four plants of L. minor and five of A. caroliniana were selected in a 50 mL Hoagland medium. For both plants, the following concentrations were used: 0.10; 1.07; 3.44; 11.16; 36.40 and 118.0 mg L-1 of each test product and a control with three replicates. The results of this study demonstrated higher sensitivity of L. minor to the tested pesticides, when compared to A. caroliniana. L. minor can be used in the monitoring of herbicides bentazon, atrazine and clomazone and pyraclostrobin-based fungicide, and A. caroliniana can be used for pyraclostrobinbased fungicides, due to the sensitivity of these organisms when exposed.
Keywords: bioindication; aquatic plants; acute toxicity; environmental monitoring; pesticide